PERILAKU KEKERASAN DALAM BERPACARAN PADA MAHASISWA DI UNIVERSITAS SUMATERA UTARA - Khair, Rizky Aulia; Suriadi , Agus (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2022)
Conceptually, violence that occurs in the whole world with a various form is an indication of power-abuse, gender inequality and domination. Dating-Violence is an act of violence that against a partner, whether physical, sexual or psychological, that are committed before marriage. Nowadays, it is a problem that is quite prominent in the world community.The objectives of this research to obtain a more specific pictures of a dating-violence behaviour.The method of this research used a descriptive-method using a qualitative approach. Descriptive research was conducted with the objectives of picturing or describing the object or phenomenon to be studied. The technique of this research was conducted using snowball sampling techniques.The samples in this research were Sekretaris Jenderal Pemerintahan Mahasiswa (PEMA). The student who experienced dating-violence at the Faculty of Social and Political Sciences, University of South Sumatera was the main sample of this research and another student, was her close-friend and families of students experiencing dating-violence. The data collection techniques using literature study, observation, and interviews. The data obtained and analysed by the researchers in order to found any new facts with a qualitative approach. The results of this research indicated that dating was no longer a matter of love and affection but rather someone tends to think that dating as a form of ownership not an exploratory process to get to know each other before stepping into a more serious step, namely marriage. Because of the opinion, it made a person committed violence to defend what was his/her own. The dating-violence were caused by several things, for examples: jealousy, infidelity, not obeying their couples’ orders. The were two kinds of violence experienced in dating: verbal violence which is a psychological violence and non-verbal violence which is physical violence.